Operations on Matrices | kullabs.com
Notes, Exercises, Videos, Tests and Things to Remember on Operations on Matrices

Please scroll down to get to the study materials.

Registration open for Special Discounts

Note on Operations on Matrices

Registration open for Mr and Miss SEE
  • Note
  • Things to remember
  • Videos
  • Exercise
  • Quiz

Addition of Matrices

Addition of Matrices
Addition of Matrices
Source:datascientist.mabs.me

If A and B are two matrices of the same order, then A and B are said to be Conformable or Compatible for addition. The sum of A and B is denoted by A+B and it is obtained by adding corresponding elements of A & B.

The matrix A+B will be of the same order as each of the matrices A and B is

If A= \(\begin{bmatrix} a_{11}&a_{12}&a_{13}\\a_{21}&a_{22}&a_{23}\end{bmatrix}\) and B= \(\begin{bmatrix} b_{11}&b_{12}&b_{13}\\b_{21}&b_{22}&b_{23}\end{bmatrix}\)

then A+B =\(\begin{bmatrix} a_{11}+b_{11}&a_{12}+b_{12}&a_{13}+b_{13}\\a_{21}+_b{21}&a_{22}+b_{22}&a_{23}+b_{23}\end{bmatrix}\)

Foe example, if A= \(\begin{bmatrix} 1&2&3\\4&-3&7\end{bmatrix}\) and B= \(\begin{bmatrix} -3&4&7\\8&9&-3\end{bmatrix}\)

Then,

A+B =\(\begin{bmatrix} 1&2&3\\4&-3&7\end{bmatrix}\) + \(\begin{bmatrix} -3&4&7\\8&9&-3\end{bmatrix}\)

= \(\begin{bmatrix} 1-3&2+4&3+7\\4+8&-3+9&7-3\end{bmatrix}\)

= \(\begin{bmatrix} -2&6&10\\12&6&4\end{bmatrix}\)


Subtraction of Matrices

Subtraction of Matrices
Subtraction of Matrices Source:calculator.mathcaptain.com

If A and B are two matrices of the same order, then they are said to be conformable for subtraction. The difference of the matrix B from A is denoted by A-B and it is obtained by subtracting the elements of B from the corresponding elements of A.

The order of the matrix A-B is same as the order of A or B.

If A = \(\begin{bmatrix}a_{11}&a_{12}&a_{13}\\a_{21}&a_{22} &a_{23}\end{bmatrix}\) and B = \(\begin{bmatrix}b_{11}&b_{12}&b_{13}
\\b_{21}&b_{22}&b_{23}\end{bmatrix}\)

then A-B = \(\begin{bmatrix} a_{11}-b_{11}&a_{12}-b_{12}&a_{13}-b_{13}\\a_{21}-b_{21}&a_{22}-b_{22}&a_{23}-b_{23}\end{bmatrix}\)

Foe example, if A =\(\begin{bmatrix} 1&2&3\\4&-3&7\end{bmatrix}\) and B= \(\begin{bmatrix} -3&4&7\\8&9&-3\end{bmatrix}\)

Then

A-B=\(\begin{bmatrix} 1&2&3\\4&-3&7\end{bmatrix}\) and B= \(\begin{bmatrix} -3&4&7\\8&9&-3\end{bmatrix}\)

=\(\begin{bmatrix} 1+3&2-1&3-7\\4-8&-3-9&7+3\end{bmatrix}\)

=\(\begin{bmatrix} 4&-2&-4\\-4&-12&10\end{bmatrix}\)

B-A =\(\begin{bmatrix} -3&4&7\\8&9&-3\end{bmatrix}\) -\(\begin{bmatrix} 1&2&3\\4&-3&7\end{bmatrix}\)

=\(\begin{bmatrix} -3-1&4-2&7-3\\8-4&9+3&-3-7\end{bmatrix}\)

=\(\begin{bmatrix} -4&2&4\\4&-12&-10\end{bmatrix}\)

 

Multiplication of a matrix by a scalar (real number)

Multiplication of Matrices
Multiplication of Matrices Source:thejuniverse.org

If A is any matrix and K is any constant or a scalar, then the matrix obtained by multiplying each element of A by K is denoted by KA and it is called the scalar multiple of A by K. 

Algebraic properties of Matrix Addition

Addition of matrices satisfy the following properties:

Closure property

If A and B are two matrices of the same order, then their A+B is also a matrix of the same order as that of A or B.

If A=\(\begin{bmatrix} 2&4\\3&5\end{bmatrix}\) and B=\(\begin{bmatrix} 6&5\\2&1\end{bmatrix}\)

Now,

A+B = \(\begin{bmatrix} 2&4\\3&5\end{bmatrix}\) + \(\begin{bmatrix} 6&5\\2&1\end{bmatrix}\)

= \(\begin{bmatrix} 8&9\\5&6\end{bmatrix}\) which is again is again a2x2 matrix. Hence the closer property is satisfied.

Commutative property

If A and B are two matrices of the same order, then A+B=B+A.

Let, A = \(\begin{bmatrix} 2&4\\6&8\end{bmatrix}\) + \(\begin{bmatrix} 7&-2\\8&4\end{bmatrix}\)

Then A+B =\(\begin{bmatrix} 2&4\\6&8\end{bmatrix}\) +\(\begin{bmatrix} 7&-2\\8&4\end{bmatrix}\)

=\(\begin{bmatrix} 9&2\\14&12\end{bmatrix}\)

B+A =\(\begin{bmatrix} 7&-2\\8&4\end{bmatrix}\) +\(\begin{bmatrix} 2&4\\6&8\end{bmatrix}\)

=\(\begin{bmatrix}9&2\\14&12\end{bmatrix}\)

∴ A+B=B+A

Hence the commutative property is satisfied.

Associative property

If A, B and C three matrices of the same order, then (A+B) + C = A +(B+C)

Existence of identity element

If A is any matrix, then three exists a null matrix 0 of the same order such that A+0 = 0+A=A.

Existence of additive inverse

If A is a matrix of any order, then there exists another matrix -A of same order such that A+(-A) =(-A) +A = 0, then additive identity.

If A and B are the matrices of the same order and K is a scalar, then

K(A+B) = KA+KB.

If A is a matrix and C,K are any two scalars, then (C+K) A=CA+KA

If C,K are any two scalars and A is a matrix, then C(KA) = (CK)A.

Solving Matrix Equations

To solve the matrix equation A + X =B where A and B are two given matrices of the same order and X is unknown, we proceed in a manner similar to numbers.

Here, A + X = B

Adding the matrix (-A)to both sides, we get

(-A)+ A+ X = (-A) + B

or, (-A+A) +X = B-A

or, 0 + X = B-A

or, X = B-A, which is the required solution.

Transpose of matrix

Transpose of Matrix
Transpose of Matrix
Source:www.thecrazyprogrammer.com

Let A be a matrix. Then the new matrix obtained by interchanging the corresponding rows and column of A is called the transpose of A. It is denoted by A' or At.

If A = \(\begin{bmatrix} a_{11}&a_{12}&a_{13}\\a_{21}&a_{22}&a_{23}\end{bmatrix}\)

Then At= \(\begin{bmatrix} a_{11}&a_{12}\\a_{13}&a_{21}\\a_{22}&a_{23}\end{bmatrix}\)

Here, the order of A' is 2 x 3 and that of At is 3 x 2. Hence, if the order of matrix A is mxn, then the order of At will be nxm. If A' is a square, matrix of order n, then At is also a square matrix of order n. If A' is a row matrix, then At is a column matrix.

Properties of transpose

  1. The transpose of the transpose of a matrix is itself. .i.e. (a') = A.
  2. The transpose of the sum of two matrices is the sum of their transposes. i.e (A+)' = A' +B'
  3. If A is any matrix and K is any number, then (KA)' = KA'.

  • The sum of A and B is denoted by A+B and it is obtained by adding corresponding elements of A &B.
  • The difference of the matrix B from A is denoted by A-B and it is obtained by subtracting the elements of B from the corresponding elements of A.
.

Very Short Questions

Soln:

(a) here given,\(\begin{bmatrix} x+y \\ x-y \\ \end{bmatrix}\)=\(\begin{bmatrix} 4 \\ 2 \\ \end{bmatrix}\)so,

x+y=4.........(i)

and x-y=2 ........(ii)

Adding two equation, we get,

2x=6 ∴ x=\(\frac{6}{2}\)=3

Putting x=3 in equation (i), we get, x

3+y=4 or, y=4-3 or, y=1

∴x=3 and y=1 Ans.

here given,

\(\begin{bmatrix} x & x+y \\ 2 & 3\\ \end{bmatrix}\)=\(\begin{bmatrix} 4 & 5 \\ 5 & 3 \\ \end{bmatrix}\)

x=4 .........(i)

and x+y=5 ..........(ii)

putting x=4 in equation (ii) we get, 4+y=5,or,y=5-4=1

∴ x=4,y=1. Ans.

Soln:

here,

\(\begin{bmatrix} x \\ -3 \\ \end{bmatrix}\)+\(\begin{bmatrix} 5 \\ y \\ \end{bmatrix}\)=\(\begin{bmatrix} 3 \\ 8 \\ \end{bmatrix}\)

or, \(\begin{bmatrix} x+5 \\ -3+y \\ \end{bmatrix}\)=\(\begin{bmatrix} 3 \\ 8 \\ \end{bmatrix}\)

or, x+5=3 and -3+y=8

or, x=3-5 and y=8+3

∴ x=-2 and y=11 Ans.

soln:

here given,

\(\begin{bmatrix} 4 & 4 \\ m & 0 \\ \end{bmatrix}\)= \(\begin{bmatrix} n & p \\ 3 & 4 \\ \end{bmatrix}\)+\(\begin{bmatrix} 2 & 3 \\ 3 & r \\ \end{bmatrix}\)

or,\(\begin{bmatrix} 4 & 4 \\ m & 0 \\ \end{bmatrix}\)=\(\begin{bmatrix} n+2 & p+4 \\ 3+3 & 4+r \\ \end{bmatrix}\)

or, \(\begin{bmatrix} 4 & 4 \\ m & 0 \\ \end{bmatrix}\)=\(\begin{bmatrix} n+2 & p+4 \\ 6 & 4+r \\ \end{bmatrix}\)

here, n+2=4..........(i) p+4=4..........(ii) m=9........(iii)

4+r=0..........(iv)

∴n=4-2=2, p=4-4=0, m=6 and r=-4

∴n=2, p=0, m=6 and r=-4 Ans.

soln:

here given, \(\begin{bmatrix} 3x-2 & 5y+4 \\ 2 & 4+2z \\ \end{bmatrix}\)=\(\begin{bmatrix} x+2 & y-4 \\ 2 & z-2 \\ \end{bmatrix}\)

or, 3x-2=x+2, 5y+4=y-4 and 4+2z=z-2

or, 3x-x=2+2 , 5y-y=-4-4 and 2z-z=-2-4

or, 2x=4, 4y=-8 and z=-6

or,x=\(\frac{4}{2}\), y=\(\frac{-8}{4}\) and z=-6

∴x=2, y=-2 and z=-6 Ans.

Here,

Given,

P=[1 0 2]

∴Transpose of P (P')=[1 0 2]'=\(\begin{bmatrix} 1 \\ 0 \\ 2 \\ \end{bmatrix}\)Ans.

 

Here,

Given,

 

Q=\(\begin{bmatrix} 3 & 4 & 0 \\ 5 & 6 & -2 \\ \end{bmatrix}\)

∴Transpose of Q (Q')=Q=\(\begin{bmatrix} 3 & 4 & 0 \\ 5 & 6 & -2 \\ \end{bmatrix}\)=\(\begin{bmatrix} 3 & 5 \\ 4 & 6 \\ 0 & -2 \\ \end{bmatrix}\)Ans.

0%
  • If the additive inverse of  (egin{pmatrix} -1&2\ 3&-4\ end{pmatrix}) is (egin{pmatrix} a&-2\ -3&b\ end{pmatrix}),find the value of a and b.

    3,7


    2,2


    4,1


    1,4


  • If the additive inverse of  (egin{pmatrix} 2&-5\ -3&6\ end{pmatrix}) is (egin{pmatrix} -2&q\ p&-6\ end{pmatrix}),find the value of p and q.

    5,3


    3,5


    2,7


    1,2


  • If the additive inverse of  (egin{pmatrix} -1&3\ -4&5\ end{pmatrix}) is (egin{pmatrix} a-1&-3\ b+3&-5\ end{pmatrix}),find the value of a and b.

    2,1


    4,5


    3,6


    1,1


  • If the additive inverse of  (egin{pmatrix} 4&-5\ 6&-7\ end{pmatrix}) is (egin{pmatrix} -4&a+2\ -6&b+3\ end{pmatrix}),find the value of a and b.

    4,5


    2,2


    1,3


    3,4


  • If  (egin{bmatrix} a & 4 \ 3 & 2 end{bmatrix}) + (egin{bmatrix} 2 & b \ 1 & -3 end{bmatrix}) = (egin{bmatrix} 4 & 1 \ 4 & c end{bmatrix}) what is the value of a, b, annd c.

    a = 6  b = 2  c = 1
    a = 2  b = -3  c = -1 
    a = -2  b = 2  c = -2
    a = -3  b = 1  c = -2
  • If A = (egin{bmatrix} 1 & 2 \ -3 & 4 end{bmatrix}) and B = (egin{bmatrix} 3 & 0 \ 0 & 4 end{bmatrix}). find the matrix C such that A - C = B.

    C = (egin{bmatrix} 4 & 6 \ -2 & 1 end{bmatrix})
    C = (egin{bmatrix} -2 & 2 \ -3 & 0 end{bmatrix})
    C = (egin{bmatrix} 8 & 5 \ 4 & 0 end{bmatrix})
    C = (egin{bmatrix} -3 & 2 \ 3 & 4 end{bmatrix})
  • If A = (egin{bmatrix} 2 & 4 \ 3 & 5 end{bmatrix}) and B = (egin{bmatrix} 6 & 5 \ 2 & 1 end{bmatrix}), then find  A + B.

    (egin{bmatrix} 8 & 9 \ 5 & 6 end{bmatrix})
    (egin{bmatrix} 3 & 6 \ -9 & 4 end{bmatrix})
    (egin{bmatrix} 3 & 5 \ -3 & 7 end{bmatrix})
    (egin{bmatrix} -2 & 2 \ -3 & 0 end{bmatrix})
  • If A = (egin{bmatrix} 0 & 0 \ 0 & 0 end{bmatrix}) what will be the A'.

    (egin{bmatrix} 0 \ 0 \ 0 \ 0 end{bmatrix})
    (egin{bmatrix} 0 & 0 \ 0 & 0 end{bmatrix})
    (egin{bmatrix} 00 & 00 \ 00 & 00 end{bmatrix})
    (egin{bmatrix} 0 & 0 & 0 & 0 end{bmatrix})
  • If A + B = (egin{bmatrix} 4 & 5 \ 6 & 7 end{bmatrix}) and B = (egin{bmatrix} 1 & 2 \ 3 & 4 end{bmatrix}), what will be the matrix A - B.

    (egin{bmatrix} -3 & 0 \ 5 & -4 end{bmatrix}
    (egin{bmatrix} 1 & 4 \ 4 & 3 end{bmatrix})
    (egin{bmatrix} 2 & 1 \ 0 &-1 end{bmatrix})
    (egin{bmatrix} 3 & 1 \ 8 & 4 end{bmatrix})
  • If A = (egin{bmatrix} x & 5 \ 3 & y end{bmatrix}) and B = (egin{bmatrix} 4 & 3 \ 5 & -2 end{bmatrix}) what will be tha value of x and y. If B' = A

    x = -2  y = 4
    x = 4  y = -2
    x = 5  y = 4
    x = 3  y = 5
  • You scored /10


    Take test again

DISCUSSIONS ABOUT THIS NOTE

You must login to reply

Forum Time Replies Report
Kala

What happens when matrix is parallel


You must login to reply

samip kadel

i confused in the exercise . question no. 1


You must login to reply